Identification and Characterization of the Antigens Expressed On the Surface of Human Erythrocytes Infected With Plasmodium falciparum - Kalantari, N (Tehran University of Medical Sciences, 2013)

(untitled)
BACKGROUND: Molecules expressed on the surface of infected erythrocytes (IE) with Plasmodium falciparum play important roles in malaria pathogenesis and immune evasion. Some of these molecules are specific adhesive ligands mediating adhesion of IE to the vascular endothelium. In the current study, the antigens exposed on the surface of IE with different isolates and various binding subpopulations of P. falciparum were studied. METHODS: A pooled hyper immune serum (HIS) from Malawian adults and eluted antibodies from the surface of the homologous and heterologous parasites were used. The parasite surface molecules were analyzed by Immuno-Gold-Silver enhancement (IGSE) and Western blotting. Mini-column cytoadherence method was used to select various parasite-binding subpopulations. RESULTS: Surface antigens of all the isolates were recognized by HIS and high recognition of antigens was observed in all isolates with homologous eluted antibodies. Western blot analysis showed that the eluted antibodies reacted with a small subset of antigens compared with HIS. Three bands, PfEMP-1, were detected in the Triton X- insoluble fraction of the ICAM-1 binding subpopulation. Another interesting band was ∼ 52-55 kDa in various isolates of P. falciparum. This molecule as defined by its low molecular weight, Triton X-100 solubility, surface location and sensitivity to 1 mg/ml trypsin. CONCLUSION: The IE's surface antigens differed in parental population compared with the selected subpopulations. These molecules could induce isolate-specific immunity. Antibodies purified from the surface of IE can be used as specific reagents to investigate parasite-derived proteins expressed on the surface of IE.